Pemberdayaan Masyarakat Desa Melalui Pembuatan Sabun Mandi Ramah Lingkungan dari Lidah Buaya - Destiartono, Mohamad Egi (Yayasan Sagita Akademia Maju, 2025)
Aloe vera is a horticultural plant that has a number of health benefits, especially for skin and hair health. Whilst aloe vera grows abundantly in rural areas, it is not widely used for daily activities or economic benefits. Hence, this community service aims to educate village communities regarding the health and economic potential of aloe vera for bath soap. This community service was conducted by employing two approaches, namely lecture and tutorial methods, which are integrated with the Kuliah Kerja Nyata (KKN) program. The specific location of the activity is Plesan Village, Nguter District, Sukoharjo Regency. The audience for this community service is rural women. The results of the community service activities are: (1) rural communities are educated in terms of the benefits of aloe vera from a health perspective: (2) village communities understand the economic potential of aloe vera: (2) rural communities, particularly women, can make bath soap from aloe vera.